Urgensi pembelajaran bahasa Arab dalam memahami Al-Qur’an - Sa’diyah, Lu’lu’atun Nadhirotus (Maliki Interdisciplinary Journal, 2024)
Arabic, as the language of the Qur’an, plays a very important role in Islam. This article discusses the urgency and benefits of learning Arabic for a deeper understanding of the Qur’an. Correct textual understanding is not only essential for Muslims to properly perform worship, but also enriches their knowledge of Islamic principles. Learning Arabic provides direct access to the primary sources of Islamic teachings, namely the Qur’an and Hadith. Without an adequate understanding of this language, many meanings, nuances and interpretations can be lost or misunderstood. In this context, Arabic is not only a means of communication, but also the key to unlocking the depth and richness of Islamic teachings. The article also explores various effective methods in learning Arabic, from traditional approaches to the use of modern technology. It also discusses the challenges often faced by learners, especially among non-native Arabic speakers, and how they can overcome these obstacles through effective learning strategies and community support. Learning Arabic has a significant impact on the spiritual and intellectual life of a Muslim. By understanding the language of the Qur’an, Muslims can access deeper and more accurate knowledge of the teachings